2018
DOI: 10.21608/ajas.2018.8086
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plant Spacing and Weed Control Treatments on Yield, Quality of Soybean (Glycine Max L.) and Associated Weeds Characters under Middle Egypt Conditions

Abstract: The present study was carried out on soybean var. Giza 111 atthe Experimental Farm of Faculty of Agriculture, El-Minia University during the summer seasons of 2015 and 2016, to study the impact of plant spacing and weed control treatments on weed control, yield and quality of soybean. The treatments include rows and plant spacing (density) as P 1 : 60×4cm (175000 plant fed -1 ), : unweeded check and W 10 : weed free for whole seasons. This study was carried out in a strip-plot design with three replications. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Our results indicate that all chemical herbicides at pre and/or post-emergence were effective compared to the untreated check. The reduction in dry weight of broad-leaved and grassy weeds may be ascribed to the inhibitory influence of herbicidal treatments on the growth stages and development of associated weeds [34,53]. We showed that the imazethapyr (T 4 ) and/or bentazon + clethodim (T 3 ) with I 1 treatment gave the highest percent reduction in dry weight of annual weeds at 60 and 80 days after sowing (DAS).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Our results indicate that all chemical herbicides at pre and/or post-emergence were effective compared to the untreated check. The reduction in dry weight of broad-leaved and grassy weeds may be ascribed to the inhibitory influence of herbicidal treatments on the growth stages and development of associated weeds [34,53]. We showed that the imazethapyr (T 4 ) and/or bentazon + clethodim (T 3 ) with I 1 treatment gave the highest percent reduction in dry weight of annual weeds at 60 and 80 days after sowing (DAS).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, using I 2 resulted in the lowest values. This result may be attributed to less irrigation water, the rate of soil water absorption by plants becomes less than the rate of evapotranspiration, consequently leading to reduced photosynthesis, decreased seed filling, and decreased seed yield may occur [34]. The application of 100% or 90% of water requirement provides soybean plants with sufficient irrigation levels with necessary nutrients for the processes of cell division and enlargement as well as for meristematic activity [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…herbicides, such as clethodim, cycloxydim, fenoxaprop-p-ethyl, fluazifop-p-butyl, quizalofop-p-ethyl, propaquizafop, imazamox, oxasulfuron, and tifensulfuron-methyl, have been registered for weed control in the soybean [22]. Weeds can be most effectively managed in soybeans with a well-planned program that includes a detailed analysis of the field situation [23]. The aim of this study was to examine the efficacy of different herbicide combinations in soybean and their phytotoxicity on a crop, and also to assess the economic feasibility of chemical weed control.…”
mentioning
confidence: 99%